Green signs for biotechnology-based industries in PH - Garcia, Mheda G.; National Biotechnology Week 2012 Cubao, Quezon City).
The article features a summary of the 8th National Biotechnology Week (NBW) where symposiums and exhibits promoting biotechnology products developed by Filipinos for Filipinos specifically for better health of the people, and protection and conservation of the environment. The event with the slogan "OK ang 5K (Kalikasan, Kalusugan,Kagandahan,Kabuhayan at Kaunlaran) sa Pangkalahatang Kalusugan: Mamamayan at Kalikasan," was spearheaded by DOH Secretary Enrique T. Ona.
Keywords: Biotechnology -- Philippines; Agricultural biotechnology -- Philippines; House Bill 844.